Effect Of Work Ethos And Compensation On Employees' Professional Commitment - S Supardi; Y Yulianah; Joko Ariawan (Universitas Dharma Wacana, 2022)
This study aims to determine the effect of work ethic and compensation on the professional commitment of the Convenience Store Employees at Sorek 1. The type of data used in this study is quantitative data obtained from questionnaires distributed and related to the problems studied. The population in this study were all general employees of 47 people, so the sampling technique in this study used a saturated sampling technique or census sampling, where all members of the population were sampled. The data analysis technique used to test the hypothesis is simple linear regression analysis and data quality test.Based on the results of data processing using statistical calculations, the results of the model analysis are as follows, Y = -0.717 + 0.857 X1 + 0.762 X2. The work ethic t-test with a t-count value of 8.437 > t-table 2.024 and a sig value of 0.000 <0.05, indicates that work ethic has a positive and significant effect on professional commitment. And the t arithmetic value is 6.286 > t table 2.024 with a sig value of 0.002, it can be said that compensation has a positive and significant effect on employee professional commitment. Test the coefficient of determination above, the value of Adjusted R Square is 0.685 or 68.5%. This shows that work ethic and compensation or independent variables are able to influence employee professional commitment or the dependent variable is 68.5%.